The Prognostic Consequence of Red Cell Distribution Width in Acute Pancreatitis - Aditya Prakash ,; Binay Kumar Shah,; Ang Dali Sherpa,; Rahul Singh, (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Acute pancreatitis is commonly a self-limiting disease but, about 25% of patients consequently develop a severe pancreatitis which leads to increase mortality. The available Scoring system is use to predicate severity of the Acute Pancreatitis, which is used for early diagnosis and management. Aim of this study is to assess the association of red blood cell distribution width (RDW) with severity and mortality in patients of acute pancreatitis. MATERIAL AND METHODS This retrospective study was carried out in Department of Surgery of National Medical College and Teaching Hospital. A total of 50 patients with diagnosis as acute pancreatitis over period of March 2020 to February 2022 was included. History and detailed clinical examination was performed as per the working proforma. Blood investigation was done. Data analysis was done using SPSS (Statistical Package for social sciences), version 25. RESULTS Mean age was 39.03 years. 68% cases were female. Acute Biliary was the most common cause. Mean RDW was 12.461, 14.50 and 15.309 in mild, moderate and severe Pancreatitis respectively with a p value of <0.001 showing signiﬁcant association of RDW and severity of Pancreatitis. Mean RDW in alive was 13.046 and 16.625 in death with a p value of <0.001 showing signiﬁ- cant association between RDW and outcome of acute Pancreatitis. CONCLUSION RDW is a predictor of severity in patients with severe acute pancreatitis.